The Effectiveness of Light Sports/ Light Exercise and The Use Of Turmeric Acid - Titin Eka Nuriyanah; Faridah Hanum (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
Disminorea defined as pain started right on or before the start of menstrual period such as cramps and corrugated pain in the lower abdomen, spread onrear downwaist and you feel tingling sensation in the pelvicarea and surrounding areas.Women who are experience pain during menstruation require non-pharmacological therapies such as herbs asam kunyit and also exercise such as light sport / light exercise Analyze the effectiveness light sport / light exercise and the use of kunyit asam to decrease dysminoreapain in Fakultas Universitas Muhammadiyah students This study was an experimental study using a qualitative approach with pre and post test methods. With the number of respondents 60 respondents. Collecting data using questionnaires, the data were tested using t-test The results of the study most respondents experienced a decrease in pain after day 2 and 3 after using kunyit asam with P = 0.000 and a day I did not decrease pain with P = 0.014. The results of the study do light exercise is more effective from the first day up to day 3 with a P value = 0.000 By doing light exercise rather than the use of kunyit asam is more effective to decrease dysmenorrhea pain Increasing the awareness of young women about the importancedoing light sport / light exerciseto reduce pain disminorea Key Ward : Dysminorea, Light Exercise, Turmeric Acid